2015
DOI: 10.1007/978-3-319-15856-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Recognition and Implantation of the Conceptus in the Mare

Abstract: Few, if any, biological processes are as diverse among domestic species as establishment of early pregnancy, in particular maternal recognition of pregnancy. Following fertilization and initial development in the mare oviduct, selective transport of the embryo through the uterotubal junction driven by embryo-derived PGE2 occurs. Upon arrival in the uterus, an acellular glycoprotein capsule is formed that covers the embryo, blastocyst, and conceptus (embryo and associated extraembryonic membranes) between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…Moreover, pathway analysis of the same set of miRNAs revealed that they are associated with Wnt signaling pathway and oxytocin receptor mediated signaling pathway, among others. Interestingly, it has been reported that oxytocin responsiveness is altered during early equine pregnancy, and reduced expression of the oxytocin receptor (OXTR) seems to be regulated at the posttranscriptional level rather than the transcriptional level [50]. Our prediction suggests that these miRNAs are potentially involved in oxytocin receptor mediated signaling pathway during early pregnancy in the mare.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, pathway analysis of the same set of miRNAs revealed that they are associated with Wnt signaling pathway and oxytocin receptor mediated signaling pathway, among others. Interestingly, it has been reported that oxytocin responsiveness is altered during early equine pregnancy, and reduced expression of the oxytocin receptor (OXTR) seems to be regulated at the posttranscriptional level rather than the transcriptional level [50]. Our prediction suggests that these miRNAs are potentially involved in oxytocin receptor mediated signaling pathway during early pregnancy in the mare.…”
Section: Discussionmentioning
confidence: 74%
“…Embryo development can be hampered following improper progestin supply when the embryo reaches the uterus [21]. Adequate P4 concentrations are vital mediators of the appropriate embryo-maternal environment during early pre-implantation embryo development [28,29]. The 45.45% of mares may fail to become pregnant in this study because of inadequate P4 concentration during post-mating.…”
Section: Fertility Of Mares After Pgf2α Treatmentmentioning
confidence: 85%
“…This anti-luteolytic signal enables the continued production of ovarian progesterone ( Sharp et al 1997 ) and pregnancy maintenance. The downregulation of PGF 2α is due to the attenuation of intrauterine oxytocin receptor expression, and hence COX2 at a post-transcriptional level ( Klein 2015 ) ( Fig. 5 ).…”
Section: Exploration Of Lipid Pathways In Equine Cyclicity and Early ...mentioning
confidence: 99%